Evolution of the Proto Sex-Chromosome in Solea senegalensis - Rodríguez, María Esther (Int J Mol Sci, 2019)
Solea senegalensis is a flatfish belonging to the Soleidae family within the Pleuronectiformes order. It has a karyotype of 2n = 42 (FN = 60; 6M + 4 SM + 8 St + 24 T) and a XX/XY system. The first pair of metacentric chromosomes has been proposed as a proto sex-chromosome originated by a Robertsonian fusion between acrocentric chromosomes. In order to elucidate a possible evolutionary origin of this chromosome 1, studies of genomic synteny were carried out with eight fish species. A total of 88 genes annotated within of 14 BACs located in the chromosome 1 of S. senegalensis were used to elaborate syntenic maps. Six BACs (BAC5K5, BAC52C17, BAC53B20, BAC84K7, BAC56H24, and BAC48P7) were distributed in, at least, 5 chromosomes in the species studied, and a group of four genes from BAC53B20 (grsf1, rufy3, slc4a4 and npffr2) and genes from BAC48K7 (dmrt2, dmrt3, dmrt1, c9orf117, kank1 and fbp1) formed a conserved cluster in all species. The analysis of repetitive sequences showed that the number of retroelements and simple repeat per BAC showed its highest value in the subcentromeric region where 53B20, 16E16 and 48K7 BACs were localized. This region contains all the dmrt genes, which are associated with sex determination in some species. In addition, the presence of a satellite “chromosome Y” (motif length: 860 bp) was detected in this region. These findings allowed to trace an evolutionary trend for the large metacentric chromosome of S. senegalensis, throughout different rearrangements, which could be at an initial phase of differentiation as sex chromosome.